An Analysis of the Folk kurdish Tale of "Pir khar kan" with Emphasis on the Approach of Ecofeminism - Mahsa Nosrati (پژوهشنامه ادبیات کردی)
The emerging theory of ecofeminism shows sociological sensitivities as well as serious caution towards the environment and the future of the human ecosystem. Ecofeminism is based on the fundamental biological and physical commonalities of women and nature, and considers nature as a feminist issue. According to this theory, men try to dominate nature and women in connection with instrumental power and rationality, and their profit-seeking approach in the patriarchal society has caused the destruction of nature and reduced the status of women. Referring to cultural and traditional tools, ecofeminists look for symbols, signs and rituals that promote empirical discourses between the environment and women. In Kurdish culture, gender and environment have always been serious social and cultural challenges, therefore stories as a cultural tool are a suitable topic for recovering the roots and common concepts between women and nature. This research aims to analyze, with descriptive and qualitative analytical methods, the main themes of "personification", "pouring flowers from the mouth and nose when sneezing", "recovery of vision with a magical element", "women's cunning" and "falling into a well" and men's approach. In the Kurdish story "PirKharkan" with an emphasis on ecofeminism, he is also trying to remind people of the importance of women's place in society and the protection of the environment by looking at the past. The premise of this article is that the analysis of the mentioned story shows a narrative of the patriarchal society's historical effort and motivation for colonization and mutual benefit of nature and women.